Targeting aldehyde dehydrogenase for prostate cancer therapies - Ma, Miao; He, Wenyou; Zhao, Keyu; Xue, Linyuan; Xia, Siyuan; Zhang, Baotong (Frontiers in Oncology, 2022)
Prostate cancer (PCa) is the most common cancer in men in the United States. About 10 – 20 % of PCa progress to castration-resistant PCa (CRPC), which is accompanied by metastasis and therapeutic resistance. Aldehyde dehydrogenase (ALDH) is famous as a marker of cancer stem-like cells in different cancer types, including PCa. Generally, ALDHs catalyze aldehyde oxidation into less toxic carboxylic acids and give cancers a survival advantage by reducing oxidative stress caused by aldehyde accumulation. In PCa, the expression of ALDHs is associated with a higher tumor stage and more lymph node metastasis. Functionally, increased ALDH activity makes PCa cells gain more capabilities in self-renewal and metastasis and reduces the sensitivity to castration and radiotherapy. Therefore, it is promising to target ALDH or ALDHhigh cells to eradicate PCa. However, challenges remain in moving the ALDH inhibitors to PCa therapy, potentially due to the toxicity of pan-ALDH inhibitors, the redundancy of ALDH isoforms, and the lack of explicit understanding of the metabolic signaling transduction details. For targeting PCa stem-like cells (PCSCs), different regulators have been revealed in ALDHhigh cells to control cell proliferation and tumorigenicity. ALDH rewires essential signaling transduction in PCa cells. It has been shown that ALDHs produce retinoic acid (RA), bind with androgen, and modulate diverse signaling. This review summarizes and discusses the pathways directly modulated by ALDHs, the crucial regulators that control the activities of ALDHhigh PCSCs, and the recent progress of ALDH targeted therapies in PCa. These efforts will provide insight into improving ALDH-targeted treatment.